Analisis Implementasi Kebijakan Kawasan Tanpa Rokok Berdasarkan Perda Nomor 5 Tahun 2016 Di Dinas Kesehatan Kabupaten Indragiri Hilir - Perawati Perawati; Nopriadi Nopriadi; Novita Riany; Kiswanto Kiswanto; Tin Gustina (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The No Smoking Area Program (KTR) is one of the policies taken by the government to control the negative effects of smoking in the community. The purpose of this study was to analyze the implementation of the KTR policy based on Perda No. 5 of 2016 at the Indragiri Hilir District Health Office in 2020. This research uses a qualitative approach with a phenomenological design. Data collection techniques in this study were in-depth interviews, observation and document searches. The number of informants in the study was 8 people. The results showed that the implementation of the Regional Regulation on KTR in the area of Indragiri Hilir District Health Office has not been implemented effectively. This is due to several factors, namely lack of socialization, lack of availability of infrastructure, no organizational structure, no supervisory committee, and no policy against sanctions for violations. It is recommended that the Health Office complete the facilities and infrastructure, provide outreach, compile an organizational structure, form a supervisory committee, and enforce the sanctions for infringement. It is also recommended that the Health Office prepare derivatives of these perda, such as a Regent Regulation, implementing guidelines, and technical guidelines so that there is legal power.